Study on Moving Objects by Video Monitoring System of Recognition and Tracing Scheme - Peilong Xu (Institute of Advanced Engineering and Science, 2013)
In this paper a recognition and tracing scheme for moving objects by video monitoring system was studied. During moving objects recognition, Multi frame sampling method was used to establish the initial background. Edges of the moving objects were drawn according to the changes of the images, and the influence factors for edges drawing were eliminated. In the end, tracing for moving objects could be realized by recognition of morphological characteristics. The experiments indicate that, for field environment, the number of collected frames between 120 to 180 could get better image background. The shadows of the moving objects are the main factor which influence detection of object edges, and they could be eliminated by Shadow edge detection operator. For vehicles tracing, adjacent frame matching method could be used to reflect the time-space transformation of the vehicles. This scheme could realize the recognition and tracing of moving objects by video monitoring system effectively. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2740